The creative enterprise of mathematics teaching research : elements of methodology and practice : from teachers to teachers - Czarnocha, Bronislaw (SensePublishers, 2016)
The Creative Enterprise of Mathematics Teaching Research presents the results and methodology of work of the teaching-research community of practice of the Bronx (TR Team of the Bronx). It has a twofold aim of impacting both teachers of Mathematics and researchers in Mathematics Education. This volume can be used by teachers of mathematics who want to use research to reflect upon and to improve their teaching craft, as well as by researchers who are interested in uncovering riches of classroom learning/teaching for research investigations. This book represents the results of a collaboration of instructors discussing their own instruction research, analyzed through a conceptual framework obtained via the synthesis of creativity research and educational learning theories, based upon the work of Piaget and Vygotsky. The editors see an urgent need for creative synthesis of research and teaching, an example of which is presented in the book. Two central themes of the book are the methodology of TR/NYCity model and creativity, more precisely, creativity of the Aha moment formulated by Arthur Koestler (1964) in a very profound but little known theory of bisociation exposed in his work "The Act of Creation". Incorporation of the theory of bisociation into classroom teaching of mathematics provides the key to enable students who may struggle with mathematics to engage their own creativity, become involved in their learning process and thus reach their full potential of excellence. Creativity in teaching remedial mathematics is teaching gifted students how to access their own giftedness